Fourier and wavelet transformation of eye movement temporal series - Astefanoaei, Corina; Creanga, Dorina Emilia; Pretegiani, Elena; Optican, L. M.; Rufa, Alessandra (2013 E-Health and Bioengineering Conference (EHB), 2013)
Saccadic eye movements, recorded from healthy human subject with an infrared camera eye tracking system, were analyzed in order to be compared with typically quasi-periodic, chaotic and random signals, theoretically generated from differential equation. To do this, we applied the Fourier transform and also the wavelet transform based on Haar function as suggested by the quasi-rectangular shape of the recorded saccadic signal. Both computational applied tests revealed that the investigated temporal data series can't be classified into none of the theoretical cases.